2021
DOI: 10.1177/10760296211040868
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Risk Prediction Model for Hospital-Acquired Pulmonary Embolism in Hospitalized Patients

Abstract: The purpose of this study is to establish a novel pulmonary embolism (PE) risk prediction model based on machine learning (ML) methods and to evaluate the predictive performance of the model and the contribution of variables to the predictive performance. We conducted a retrospective study at the Shanghai Tenth People's Hospital and collected the clinical data of in-patients that received pulmonary computed tomography imaging between January 1, 2014 and December 31, 2018. We trained several ML models, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In addition, there is still a major inconsistency among the potential predictors of VTE identified by previous studies [ 24 ]. In this context, machine learning (ML) techniques, which can identify complex (non-linear) correlations among potential predictors, may be useful tools [ 25 ]. However, to the best of our knowledge, the use of ML as an approach to assess VTE predictors in COVID-19 patients has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is still a major inconsistency among the potential predictors of VTE identified by previous studies [ 24 ]. In this context, machine learning (ML) techniques, which can identify complex (non-linear) correlations among potential predictors, may be useful tools [ 25 ]. However, to the best of our knowledge, the use of ML as an approach to assess VTE predictors in COVID-19 patients has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Non-ICU COVID-19 patients with a D-dimer level ≥2,000 ng/mL are considered to need further examination to rule out PE (Thoreau et al, 2021). Data from a 3,619 study of PE showed that high D-dimer levels had almost been proved to be significantly associated with the severity of PE (Hou et al, 2021). Another trial looked at the percentage decrease in D-dimer concentration between at diagnosis and within 1 month of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…that explored in-and post-hospital VTE at different time periods, were included (see Supplementary Table 1). Diagnosis of VTE was either confirmed via International Classification of Diseases (ICD) codes 31,32,36,37 , administration of anticoagulation treatment 36,37 or imaging studies 30,33,35,49 . Most of the published studies are retrospective and are derived from a single institution except for 36,50 which are derived from multiple centers.…”
Section: Prediction Of Vte Risk In Non-surgical Hospitalized Patientsmentioning
confidence: 99%
“…Most of the published studies are retrospective and are derived from a single institution except for 36,50 which are derived from multiple centers. Ma et al 35 and Hou et al 33 addressed the temporal characteristics of the laboratory tests, such as min, max, last measurement, and time windows for some dynamic laboratory features. Most of the studies did not provide clear information regarding feature selection, 31,37,49,50 preprocessing and missing values handling 31,36,37,49,50 and hyperparameter tuning 31,33,36,49 .…”
Section: Prediction Of Vte Risk In Non-surgical Hospitalized Patientsmentioning
confidence: 99%
See 1 more Smart Citation